A study on macroeconomic factors that affect household debt in Malaysia / Fatini Adilah Faizal Amir and Nur Amirah Mohamad Nasir - Faizal Amir, Fatini Adilah; Mohamad Nasir, Nur Amirah (Faculty of Business Management, 2016)
The macroeconomics factor that could affect the Household Debt in different countries has been investigated globally by researches such Debelle (2004), Mian, Sufi, & Verner (2015), Turinetti & Zhuang (2011) and Meniago, Mukuddem-Petersen, Petersen, & Mongale (2013). This study aims to extend the knowledge of the relationship and impact of macroeconomic factors such as Interest Rate (BLR), Inflation Rate (CPI), Unemployment Rate (UR) and House Price Index (HPI) towards the Household Debt to GDP in Malaysia. Simple linear regression and multiple linear regression were applied in this study in order to clarify the relationship between the macroeconomic factors with the Household Debt to GDP in Malaysia. The result obtained in this study indicates there is a positive significant relationship between Inflation Rate (CPI) with Household debt to GDP in Malaysia.